2006
DOI: 10.1007/s00436-006-0200-5
|View full text |Cite
|
Sign up to set email alerts
|

Toxocara canis larvae viability after disinfectant—exposition

Abstract: The effect of three routinely used disinfectants on the embryonary development of Toxocara canis eggs was evaluated both in vivo and in vitro. In the in vitro experiment, T. canis eggs were treated with the ethanol, sodium hypochlorite, and one commercial mix of benzalconium chloride and formaldehyde, and the embryonary development was assessed. After a period of 24 days incubation, ethanol was the best disinfectant because it prevented the development of the T. canis larvae 2 in the eggs, and sodium hypochlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 11 publications
3
26
0
2
Order By: Relevance
“…(2001) found that iodine dilutions inactivate larvae inside T. canis eggs after only short‐term exposure. Consistent with our findings, Morrondo et al. (2006) observed that 70% ethyl alcohol was highly effective in inhibiting T. canis embryonic development.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…(2001) found that iodine dilutions inactivate larvae inside T. canis eggs after only short‐term exposure. Consistent with our findings, Morrondo et al. (2006) observed that 70% ethyl alcohol was highly effective in inhibiting T. canis embryonic development.…”
Section: Discussionsupporting
confidence: 92%
“…The other two commercial disinfectants (benzalconium chloride‐ and formaldehyde‐based disinfectant) we tested had no effect on T. canis eggs, which corroborates the findings of Ayçiçek et al. (2001) and Morrondo et al. (2006).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…More precise baseline rates of development could also facilitate in vitro studies of drugs and disinfectants (e.g. Morrondo et al 2006). This study aimed to determine the lower threshold temperature for development of T. canis eggs to the infective larval stage, and the relationship between temperature and mean development rate.…”
Section: Introductionmentioning
confidence: 99%